94.7k views
1 vote
How do you solve this?

How do you solve this?-example-1
User Brunnie
by
4.7k points

1 Answer

3 votes

Answer:

1

Explanation:

I would think (I'm not sure, but it's an idea)


(x^(2) +2)/(x^(2) -1) =(x^(2) -1+1+2)/(x^(2) -1)\\\\=((x^(2)-1) +3)/(x^(2) -1)=(x^(2) -1)/(x^(2)-1)+(3)/(x^(2) -1)\\\\=1+(3)/(x^(2) -1)

so when x becomes bigger and bigger

the


(3)/(x^(2) -1)

will become smaller and smaller

to a point that it's practically 0

so the limit is 1

User Kiwi Lin
by
4.6k points